What doctors should call their patients. Issue 3 (September 1988) - Lavin, M
Abstract : The paper discusses the moral difficulties physicians encounter when determining the level of formality they will use when addressing their patients. It is argued that physicians ought not to use a patient's first name unless the patient also uses the physician's first name. In short, physicians and patients should always address each other with the same level of formality. It is argued that this is so even when patients invite physicians to address them informally.